GLP-1 receptor agonists and pancreatic beta cell apoptosis in diabetes mellitus: a systematic review and meta-analysis of preclinical studies - Rea, Nicolas; Ramdass, Prakash V. A. K. (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionDiabetes mellitus (DM) is a global health challenge characterized by progressive beta cell dysfunction. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have emerged as promising therapies, enhancing insulin secretion while potentially preserving beta cell mass by inhibiting apoptosis. However, concerns persist regarding long-term beta cell adaptation and functional exhaustion. This meta-analysis synthesizes preclinical evidence to evaluate the effects of GLP-1RAs on beta cell apoptosis in DM.MethodsFollowing PRISMA guidelines, we systematically searched Scopus, PubMed, Embase, and Google Scholar for preclinical studies assessing GLP-1RAs effects on human beta cell apoptosis. Five studies met inclusion criteria for meta-analysis. Data were extracted on apoptotic rates, and risk of bias was assessed using the OHAT tool. A random-effects model calculated pooled mean differences (MDs) in apoptosis, with sensitivity analyses and funnel plots evaluating robustness and publication bias.ResultsGLP-1RAs significantly reduced beta cell apoptosis (pooled MD: −0.10; 95% CI: −0.15 to −0.05, p = 0.0003), with high heterogeneity (I² = 100%). Sensitivity analyses confirmed consistency, with effect estimates ranging from −0.077 to −0.118 upon sequential study exclusion. Funnel plot and Egger’s test (p = 0.80) indicated no significant publication bias, though limited study numbers constrain power.ConclusionsGLP-1RAs demonstrate a robust anti-apoptotic effect on pancreatic beta cells in preclinical models, supporting their role in preserving beta cell mass. However, extreme heterogeneity and unresolved questions about long-term functional exhaustion warrant cautious interpretation. Future research should prioritize longitudinal human studies to assess clinical relevance and optimize therapeutic strategies. IntroductionSystem review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024516313, identifier CRD42024516313.